A geothermal-biomass powered multi-generation plant with freshwater and hydrogen generation options: Thermo-economic-environmental appraisals and multi-criteria optimization. (October 2022) - Hashemian, Nasim; Noorpoor, Alireza
Abstract: In the current article, a novel geothermal-biomass-powered multi-generation plant was introduced and probed through thermo-economic-environmental aspects plus multi-criteria optimization. To produce various outcomes, like electricity, heating, cooling, as well as hydrogen and freshwater, the plant took advantage of the Rankine cycle, a dual-effect absorption refrigeration unit, a proton exchange membrane water electrolyzer, and a biomass combustor. The plant's environmental consequences were reviewed based on NOx and CO2 emitting to mark the environmental advantages of burning municipal solid waste as biomass rather than coal. Owing to the investigation, the plant provided 31.68 MW direct power, 39.85 MW heating, 126.36 MW cooling, 23.3 m 3 /h freshwaters, and 88.12 kg/h hydrogen, besides 58.54% and 16.45% calculated as plant energetic and exergetic efficiencies. By applying the SPECO approach, the total product cost rate was attained at 1.629 $/s. As well, this plant had an exergo-environmental impact factor of 0.9. Moreover, a parametric study was brought out to comprehend the consequences of chief parameter changes. Eventually, a multi-criteria optimization was employed for the plant for the enhancement of the techno-economic operations. In the optimum status, the total cost rate of the product and exergetic efficiency of 1.57 $/s and 17.26% were attainable.